Simulation of obliquely incident light propagation through a general twisted nematic liquid crystal cell by the Jones matrix technique - Valyukh, S.; Slobodyanyuk, A.; Sorokin, V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
The simple Jones matrix technique was applied for finding intensity of obliquely incident light that passes through a plate of a uniaxial uniform medium that later was extended to general twisted nematic liquid crystal medium. Results of calculations were compared with the Berreman 4×4 matrix technique. Shown is the way of finding contrast viewing characteristics of nematic liquid-crystal displays. The obtained results are compared with experimental data.